The Uzbek Taakiyas in Turkey: The Religious, Social, and Economic Role of the Uzbek Taakiya in Uskudar - Bebitov Maqsud Abdirasulovich (Scientific Trends, 2025)
This article examines the political and economic aspects of the relationship between the Ottoman Empire and the Uzbek Takiyas. Special attention is given to the Uzbek Takiyas in Istanbul, focusing on state funding allocated to these institutions and the connections between Takiyah sheikhs and the imperial court. Rare archival documents from the Ottoman archives serve as the main source for this research. Although there have been previous studies on this topic [1, B. 200-202; 40-45; 38-43; 27-34], many of them have not fully utilized archival materials. The novelty of this study lies in its presentation of new information regarding not only the religious significance of the Takiyas but also their role within the political and economic system of the Ottoman Empire. In particular, the Uzbek Takiyah in Uskudar played a crucial intermediary role in the relations between the Ottomans and Central Asia. This article analyzes the social, political, and economic activities of this institution based on previously unexplored archival documents.
Keywords: Uzbek Takiyah, Ottoman Empire, Naqshbandiyya, social structure, economic relations, religious center.